2003
DOI: 10.1115/1.1530195
|View full text |Cite
|
Sign up to set email alerts
|

Solar Chimney Turbine Performance

Abstract: This project investigates the performance of solar chimney power plant turbines. A solar chimney power plant consists of a tall chimney surrounded by a transparent deck or solar collector. The sun heats the air in the collector through the greenhouse effect. A turbine extracts energy from the hot air rising up the chimney. An investigation of the requirements and operation of such turbines is needed.Correct matching of the turbine to the plant requires the determination of the turbine operational range and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…[12] The efficiency of the turbine was set at 0.85 to be consistent with other studies in the prediction of the SCPP performance. This assumed value may be a compromise, given the wide variation of operating points and different turbine configurations in practical applications.…”
Section: The Turbine Modelmentioning
confidence: 99%
“…[12] The efficiency of the turbine was set at 0.85 to be consistent with other studies in the prediction of the SCPP performance. This assumed value may be a compromise, given the wide variation of operating points and different turbine configurations in practical applications.…”
Section: The Turbine Modelmentioning
confidence: 99%
“…Using the MTFM method, the flow in the duct is also analysed to check and see that there are no adverse pressure gradients as the flow turns into the turbine as this could lead to separation at parts of the wall. This is achieved by using the interpolation method that allows values on a local orthogonal grid from the quasiorthogonal grid to be calculated using a simple linear interpolation method, by (Harms et al [21] .This approach is used in an almost identical form in the application of the streamline through flow method (STFM) and detail of the implementation is given, which done in thesis presented by Gannon [22].…”
Section: Turbine Design Of the Scppmentioning
confidence: 99%
“…The developed analytical model showed good agreement with the experimental results of the small-scale plant built in Manzanares allowing it to be used reliably in the prediction of the output of a full-scale plant. Gannon and Von Backstrom [77], [78] investigated the performance of the turbine for SCPPs. They reported that the anticipated pressure drop in a full-scale solar chimney turbine was much higher than what had previously been forecasted.…”
Section: Analytical and Simulation Studiesmentioning
confidence: 99%